Fire retardant functionalized polyol by phosphonate monomer insertion. Issue 12 (19th August 2015) - Velencoso, María M; Ramos, María J; Serrano, Angel; de Lucas, Antonio; Rodríguez, Juan F
Abstract A strategy for synthesis and functionalization of polyurethanes (PUs) is described. Polyols bearing terminal groups were prepared by anionic ring‐opening copolymerization between propylene oxide and epoxy dimethylphosphonate (POPh). The direct insertion of POPh improves the flammability of PUs. Therefore the structure, properties and flame retardant properties of polyether polyols and PUs were studied. The structure of the polyether polyols was confirmed by gel permeation chromatography (GPC), nuclear magnetic resonance spectroscopy (NMR) and matrix assisted laser desorption ionization time‐of‐flight (MALDI‐TOF). The thermal stability was determined by TGA (thermogravimetric analysis). The morphological structure was analysed by scanning electron microscope (SEM). The elemental composition of the charred residues was determined by energy dispersive x‐ray spectrometer (EDAX). The introduction of POPh presents the advantage of being able to increase the percentage of phosphorus introduced in the polyol, which slightly modifies the thermal stability of the phosphorylated foams. The temperature decreased as the phosphorus was incorporated and the percentage of char increased as well. © 2015 Society of Chemical Industry